1977
DOI: 10.1136/jnnp.40.9.843
|View full text |Cite
|
Sign up to set email alerts
|

Systemic vascular responses to increased intracranial pressure: 2 The `Cushing' response in the presence of intracranial space-occupying lesions: systemic and cerebral haemodynamic studies in the dog and the baboon

Abstract: SUMMARY Continued expansion of an artificial space-occupying lesion produced further increases in mean supratentorial and infratentorial pressures associated with increases in mean arterial pressure, heart rate, and systemic vascular resistance-the 'Cushing' or systemic hypertensive response. These primary changes resulted in an increase in transtentorial pressure gradient and a decrease in arrhythmia index. Immediately before the onset of the systemic hypertensive response, supratentorial perfusion pressure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
3

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 16 publications
(26 reference statements)
0
21
0
3
Order By: Relevance
“…These authors thus concluded that the CR is a very late phenomenon and represent the school of thought that the CR is indeed a 'pre-terminal event followed rapidly by circulatory failure'. 5 …”
Section: Description Of the Classical Crmentioning
confidence: 97%
See 1 more Smart Citation
“…These authors thus concluded that the CR is a very late phenomenon and represent the school of thought that the CR is indeed a 'pre-terminal event followed rapidly by circulatory failure'. 5 …”
Section: Description Of the Classical Crmentioning
confidence: 97%
“…This being the case, there is little doubt that CR is therefore associated with a grim prognosis. 3,4 Fitch et al 5 in his early study in 1977 identified the systemic hypertensive response as the last of six indices which evolve in a certain sequence from the start of a rise in ICP, together with bradycardia, arrhythmia, papillary constriction, unilateral pupillary dilatation and an increase in pulse pressure. He also noted that the 'period of systemic hypertension did not appear to produce any worthwhile improvement in the perfusion pressure or in the blood flow in the supratentorial compartment', although he found augmentation in infratentorial perfusion.…”
Section: Description Of the Classical Crmentioning
confidence: 99%
“…[10][11][12][13] Some animal studies suggest Cushing's response is a late feature, when ICP approaches mean arterial pressure, signalling breakdown of cerebral autoregulation. [14][15][16][17] In this situation, hypertension leads to further increase of ICP, adversely influencing cerebral perfusion. [14][15][16][17] It is likely that both the level of maximal ICP, and the rate of ICP change influence the hemodynamic response.…”
Section: Case Reportmentioning
confidence: 99%
“…[14][15][16][17] In this situation, hypertension leads to further increase of ICP, adversely influencing cerebral perfusion. [14][15][16][17] It is likely that both the level of maximal ICP, and the rate of ICP change influence the hemodynamic response. Animal studies showed "classic" Cushing's response to be apparent and beneficial to CPP only with gradual increases in ICP, with maximal ICP staying within the limits of cerebral autoregulation.…”
Section: Case Reportmentioning
confidence: 99%
“…Healthy, smaller-sized or older animals are more likely to develop hypothermia (Lee 2017), therefore we tested and excluded age and bodyweight as potential confounding factors. One possible cause for the difference in heart rate between the two groups is a Cushing reflex secondary to increased intracranial pressure leading to heart rate reduction (Fitch et al, 1977). Another possible explanation would be a destruction of the hypothalamus by the macroadenoma.…”
mentioning
confidence: 99%